Immanuel Kant: freedom, sin, forgiveness - Kuzin I. V. (Кантовский сборник, 2010)
This article offers a comparative analysis of Kant's moral philosophy and the philosophy of Sade revealing the paradoxes of the categorical imperative. The satisfaction of the requirement of the categorical imperative is, on the one hand, a single and unique act and, on the other hand, a permanent and universal one. Although the familiarity with the categorical imperative does not always result in a moral action, the familiarity itself alongside the idea of forgiveness may be considered as a manifestation of morality and freedom.